Taxonomic revision of Collaria Provancher, 1872 (Hemiptera: Miridae) with the description of a new species from the Afrotropical region - Morales, Irina; Ferreira, Paulo S. F.; Forero, Dimitri (Zootaxa, 2016)
Collaria Provancher (Mirinae: Stenodemini) is a genus of grass-feeding plant bugs with 14 recognized species. The present work presents a taxonomic revision of the genus, including redescriptions of all species and the description of C. schwartzi sp. nov. from Central and Eastern Africa. The female genitalia of C. boliviana and C. villiersi, and the male and female genitalia of C. improvisa and C. obscuricornis are described for the first time. New distributional records for the Neotropical region are provided. A key to separate all the species and illustrations of the male and female genitalia of almost all the species are included. We highlight the need to produce better series of specimens with accurate host-plant data.